De-stigmatizing marriage and family therapy for those justice- involved - Tadros, Eman (The journal of forensic psychiatry & psychology, 2025)
Widespread misconceptions surrounding incarceration and its intersection with mental health negatively impact the reentry population, particularly through the use of stigmatizing language, which impedes successful reintegration into society. This stigmatization often leads to maladaptive behaviors or recidivism among returning citizens. It is imperative that Marriage and Family Therapists (MFTs) and correctional staff expand their cultural awareness when working with this population to avoid perpetuating harmful stereotypes. This paper examines the challenges faced by returning citizens and their families, emphasizing the detrimental effects of the current gaps in awareness and the urgent need to combat stigma. This paper proposes actionable steps for policymakers, including the integration of comprehensive services for incarcerated individuals, enhanced psychoeducation and training for MFTs, and thorough mental health evaluations and classifications. These interventions aim to improve outcomes for individuals reentering society. Incarceration impacts not only the individual but the entire family system. Attending marriage and family therapy is at times stigmatized in our society, thus when individuals experience stigma due to their incarcerated loved ones this stigma is compounded. This article provides clinical and policy implications for de-stigmatizing therapy.